Evolving policy paradigms of middle leadership in Scottish and Irish education: implications for middle leadership professional development. (8th August 2019) - Forde, Christine; Hamilton, Gillian; Ní Bhróithe, Máire; Nihill, Mary; Rooney, Anna Mai
ABSTRACT: Middle leadership is a dynamic area of policy in Scottish and Irish education to build leadership capacity. This article reports on a critical policy analysis of sequential sets of Scottish and Irish policy on middle leadership to identify codes of meaning. Two aspects are reported: (1) constructions of the purposes of middle leadership and (2) key themes in changing policy paradigms. While there is a development of policy ideas from delegated tasks to management functions to leadership for learning, there is little on the practice of leading learning. The findings are reviewed to identify issues related to middle leadership professional development.